Occurrence, Distribution, Evolutionary Relationships, Epidemiology, and Management of Orthotospoviruses in China - Zhang, Zhongkai; Zheng, Kuanyu; Zhao, Lihua; Su, Xiaoxia; Zheng, Xue; Wang, Tiantian (Frontiers in Microbiology, 2021)
Orthotospoviruses are responsible for serious crop losses worldwide. Orthotospoviral diseases have spread rapidly in China over the past 10 years and are now found in 19 provinces. Currently, 18 Orthotospovirus species have been reported in China, including eight newly identified species from this genus. The number of new highly pathogenic Orthotospovirus strains or species has increased, likely because of the virus species diversity, the wide range of available hosts, adaptation of the viruses to different climates, and multiple transmission routes. This review describes the distribution of Orthotospovirus species, host plants, typical symptoms of infection under natural conditions, the systemic infection of host plants, spatial clustering characteristics of virus particles in host cells, and the orthotospoviral infection cycle in the field. The evolutionary relationships of orthotospoviruses isolated from China and epidemiology are also discussed. In order to effectively manage orthotospoviral disease, future research needs to focus on deciphering the underlying mechanisms of systemic infection, studying complex/mixed infections involving the same or different Orthotospovirus species or other viruses, elucidating orthotospovirus adaptative mechanisms to multiple climate types, breeding virus-resistant plants, identifying new strains and species, developing early monitoring and early warning systems for plant infection, and studying infection transmission routes.